2005
DOI: 10.1603/0046-225x-34.1.205
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Host Suitability of SomeBrassicaCultivars for the Whitefly,Aleyrodes proletella(Homoptera: Aleyrodidae)

Abstract: Four cultivars of broccoli (Brassica oleracea L. variety ÔitalicaÕ), two cultivars of early caulißower (Brassica oleracea L. variety ÔbotrytisÕ), four cultivars of late caulißower, and one cultivar of red cabbage (Brassica oleracea L. variety ÔcapitataÕ) were screened to determine some reproductive parameters of Aleyrodes proletella L. in a no-choice assay. The highest and lowest oviposition rates and production of pupae and adults were obtained with late caulißower (cultivar Picasso) and red cabbage (cultivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The increasing resistance may be linked to the time of natural whitefly infestation in the field, suggesting that cabbage plants invest in direct defense responses against the cabbage whitefly when needed (Boege and Marquis 2005). Age dependent resistance was not recognized in earlier studies (Ramsey and Ellis 1996;Nebreda et al 2005). In those studies, experiments were performed at the six true leaf stage, which is comparable to our 6 week old plants stage.…”
Section: Whitefly Resistance In Wild Relatives Of B Oleraceamentioning
confidence: 54%
“…The increasing resistance may be linked to the time of natural whitefly infestation in the field, suggesting that cabbage plants invest in direct defense responses against the cabbage whitefly when needed (Boege and Marquis 2005). Age dependent resistance was not recognized in earlier studies (Ramsey and Ellis 1996;Nebreda et al 2005). In those studies, experiments were performed at the six true leaf stage, which is comparable to our 6 week old plants stage.…”
Section: Whitefly Resistance In Wild Relatives Of B Oleraceamentioning
confidence: 54%
“…Several experiments were conducted to record insect development on the same cultivars of B. oleracea at eight constant temperatures: 16, 18, 20, 22, 24, 26, 28, and 30ЊC. Following the methodology of a previous study (Nebreda et al 2005), ten 7-d-old females, all from the same colony, were introduced into each of 10 clipcages (Muñ iz and Nombela, 2001) and attached to the under-surface of one leaf (one cage per plant; Þve plants per cultivar). The caged females were held in the climatic chamber for a 10-h oviposition period at the above-mentioned conditions and subsequently removed.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study with A. proletella (Nebreda et al 2005), it was observed that Marathon and Agripa, two of the most cultivated brassica crops in Navarra (Spain), were the less and the most affected cultivars, respectively. The main objective of this study was to contribute to clarify the variation in growth and development of A. proletella with regard to these cultivars, so that effective management strategies can be developed in those places where these plants and whiteßies are present.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…For example, the bird cherry-oat aphid, Rhopalosiphum padi (Linnaeus) (Homoptera: Aphididae), an important pest of cereals (Lowles, 1995), is used as alternative prey for aphid parasitoids for biological control in greenhouse vegetables (e.g., Neil et al, 1997;Hansen, 2000). Similarly cabbage whitefly, Aleyrodes proletella (L.) (Hemiptera: Aleyrodidae), a serious pest of cabbage (Nebreda et al, 2005), could be used as an alternative host for E. formosa for biological control of greenhouse whiteflies in greenhouse cucumber (Laska and Zelenkova 1988; van der Linden and van der Staaij, 2001).…”
Section: The Alternative Foodmentioning
confidence: 99%